Algerian coastal cities in the 10th century AH / 16 AD when Marmol Karbakhal and Abi al-Hassan al-Tamqrouti - Comparative study- - belamri, Fateh (The Algerian Historical Journal, 2026)
These pages are about Algerian coastal cities in the 10th century AH / 16 AD in the eyes of a European writer, who is like a traveler who lived a good period of time in the North African region, compared to what was mentioned by a Moroccan ambassador who passed through the coast of Algeria and landed in many of its cities, heading to Constantinople on a diplomatic mission Through this, we decided to present these cities, which are the outposts of Algeria, according to what both writers have written about them; European and Arab, trying to identify the points of similarity and difference between them in this matter. Accordingly, the problem revolves around the definition of the two writers and their sources, and how was their view of these cities? What are the factors that influenced their writing about these cities? What are their sources for that other than observation and